2021
DOI: 10.30827/cpag.v31i0.17010
|View full text |Cite
|
Sign up to set email alerts
|

Una revisión del megalitismo del valle del río Gor desde los GIS y el análisis estadístico. Nuevos datos y nuevas preguntas

Abstract: El conjunto megalítico del valle del río Gor (Granada) es una de las mayores agrupaciones dolménicas que se encuentran en Europa. A pesar de su gran entidad, encontramos aún en la actualidad grandes lagunas en la investigación de estas necrópolis, así como una evidente falta de medidas de conservación de las mismas. En este trabajo presentamos los resultados de una nueva campaña de documentación de estos megalitos realizada en el verano de 2019 con un triple fin: el registro y documentación de la totalidad de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…While statistical analyses suggest a high probability that the 230 new locations correspond to previously unknown burial mounds, the surface survey found that, out of 25 predicted burial mounds in the sample areas, at least nine of them correspond to partially destroyed megalithic graves, possibly after the first archaeological interventions therefore, 83 new burial mounds could be present in the entire study area. This prediction would increase the number of preserved dolmens in the area from 151 (Cabrero et al, 2021) to 234-close to the estimates from old catalogues (Spanedda et al, 2014). Not only has it improved the accuracy of identifying previously documented archaeological structures, it has also reduced the ratio of false positives (Berganzo-Besga et al, 2021;Davis et al, 2021;Trier et al, 2021;Verschoof-van der Vaart et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…While statistical analyses suggest a high probability that the 230 new locations correspond to previously unknown burial mounds, the surface survey found that, out of 25 predicted burial mounds in the sample areas, at least nine of them correspond to partially destroyed megalithic graves, possibly after the first archaeological interventions therefore, 83 new burial mounds could be present in the entire study area. This prediction would increase the number of preserved dolmens in the area from 151 (Cabrero et al, 2021) to 234-close to the estimates from old catalogues (Spanedda et al, 2014). Not only has it improved the accuracy of identifying previously documented archaeological structures, it has also reduced the ratio of false positives (Berganzo-Besga et al, 2021;Davis et al, 2021;Trier et al, 2021;Verschoof-van der Vaart et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…The starting point for this work is the cited catalogue carried out in 2019, which focused on burial mounds placement, associated terrain characteristics and other variables also related to the territory such as the orientation of the dolmens relative to the main geographic landmarks. In the same way, an evaluation of dolmen preservation status was made (Cabrero et al, 2021). The results gave rise to several questions related to preservation-disappearance patterns of these burial mounds.…”
Section: The Megalithic Landscape Of the Gor River Valleymentioning
confidence: 99%
See 3 more Smart Citations